Keberlanjutan: Analisis Etika Bisnis dalam Budidaya Kelapa Sawit di PT Astra Agro Lestari - Septiana Dina Mahiro; Kunadi Kunadi; Yennyka Leilasariyanti; Gyska Indah Harya; Laqma Dica Fitriani (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The palm oil industry is one of the main pillars of the Indonesian economy. However, despite its crucial role, the industry also faces pressures related to sustainability and ethics in palm oil cultivation practices. Issues related to ethics in palm oil cultivation practices in Indonesia have emerged, drawing national and international attention, such as unsustainable land clearing and the resulting negative environmental and social impacts, such as flooding. This indicates unethical cultivation practices. AALI is one of the palm oil companies responding to demands for cultivation practices that comply with standards and ethics. AALI has a commitment to ethical cultivation practices ranging from biodiversity protection, deforestation prevention, fulfillment of workers' rights, to community engagement mechanisms. The purpose of this study is to analyze the application of ethics in palm oil cultivation practices at PT Astra Agro Lestari. Through a literature study method with a Systematic Literature Review (SLR), the results will be obtained. AALI strives to integrate ethical principles into palm oil cultivation practices. Through the application of ethics, AALI helps AALI consistently fulfills its commitments, thereby minimizing social and environmental risks, strengthening relationships with stakeholders, and enhancing the company's reputation and competitiveness at the national and global levels.